2013
DOI: 10.1016/s0140-6736(13)62222-9
|View full text |Cite
|
Sign up to set email alerts
|

Associations between health and sexual lifestyles in Britain: findings from the third National Survey of Sexual Attitudes and Lifestyles (Natsal-3)

Abstract: SummaryBackgroundPhysical and mental health could greatly affect sexual activity and fulfilment, but the nature of associations at a population level is poorly understood. We used data from the third National Survey of Sexual Attitudes and Lifestyles (Natsal-3) to explore associations between health and sexual lifestyles in Britain (England, Scotland, and Wales).MethodsMen and women aged 16–74 years who were resident in households in Britain were interviewed between Sept 6, 2010, and Aug 31, 2012. Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
148
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(161 citation statements)
references
References 42 publications
11
148
0
2
Order By: Relevance
“…Some population-based surveys have specifically examined the importance of sexuality with respect to health and wellbeing, with studies from both the US (Lindau et al, 2007) and UK (Mercer, Tanton, et al, 2013;Mitchell et al, 2013) indicating that many older adults are engaged in intimate relationships and regard sexuality as an important part of life. While it is recognized that sexuality in later life is influenced by physiological, situational and attitudinal dimensions (Morley & Tolson, 2012), little is known about how sexuality relates to the ageing process more generally.…”
Section: Introductionmentioning
confidence: 99%
“…Some population-based surveys have specifically examined the importance of sexuality with respect to health and wellbeing, with studies from both the US (Lindau et al, 2007) and UK (Mercer, Tanton, et al, 2013;Mitchell et al, 2013) indicating that many older adults are engaged in intimate relationships and regard sexuality as an important part of life. While it is recognized that sexuality in later life is influenced by physiological, situational and attitudinal dimensions (Morley & Tolson, 2012), little is known about how sexuality relates to the ageing process more generally.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 In addition, within the UK, around 80% of adult life is spent in very good or good health which is associated with being more sexually active than when in poor health. [7][8][9],* Large scale UK-based survey data indicates that 77.7% of men and 53.7% of women from age 50 to over 90 were sexually active in the last year. 9 The sexual domain of healthy ageing remains a largely underexplored area, lacking relevant evidence to shape intervention design and service provision.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the two largest studies on sexual health and function that include older persons are the National Social Life, Health, and Aging Project (NSHAP) [1] in the USA and the third National Survey of Sexual Attitudes and Lifestyles (Natsal-3) [5] in the UK.…”
Section: Sexual Behaviourmentioning
confidence: 99%
“…The Natsal-3 reported that men and women with a longstanding illness, ≥2 chronic conditions, a BMI >35 kg/m 2 or who walk up stairs with difficulty due to a health problem were significantly less likely to report sexual activities in the prior 4 weeks than those who did not report these issues. [5] Depression, coronary artery disease, renal failure, lower urinary tract symptoms in women, hyperprolactinaemia, diabetes mellitus, primary or secondary hypogonadism in men, and neurological diseases, e.g. cerebrovascular disease and Parkinson's disease, are all associated with reduced sexual desire and arousal.…”
Section: Health and Sexual Behaviourmentioning
confidence: 99%
See 1 more Smart Citation